(untitled) (Eurasian Journal of Ecology, 2023)
The article considered the current state of the soil cover of the Southern Balkhash region. Morphological features of soil images are described, mechanical and chemical composition is determined. According to the morphological characteristics of the soil, it was found that the first image soil is gray soil, the second image soil is grayish yellow sandy soil, and the third image soil belongs to the Sandy orange soil type. The composition of all soil images was dominated by fine sand and coarse dust fractions. Since the chemical composition of the soil is one of its main agrochemical properties, the content of nutrient elements has been determined. As a result, it was found that nitrogen – low, phosphorus – medium, potassium – was sufficiently contained. The content of nutrient elements was higher in the surface layers of the soil than in the lower layers. The humus content is very low. It was found that the reaction of the soil medium is alkaline. The alkalinity of soils increased with the depth of the soil. Soil images on absorbed bases were characterized by a set of absorbed bases of low size (5 - 10 ml- eqv/100 g of soil). The water filtration of the soil was dominated by bicarbonate (NSO3-) ions and CA cation. In terms of the set of salt content, all soil images belong to the category of unsalted, that is, the set of salts was below 0.2%. Keywords: humus, nutrient elements, soil morphology, absorbed bases, soil environment reaction, soil salinization, water filtration.